“Very Misunderstood”: Self-Perceived Social Communication Experiences of Autistic Young Adults - Aieshea L. Banks; Karen J. Mainess; Heather Javaherian; Misaki N. Natsuaki (Youth)
Historically, society has labeled social communication differences in autistic individuals as disordered by comparing them to the social communication behaviors of the predominant non-autistic population. This study explores how autistic young adults view their social communication experiences and how their differences impact them when navigating social situations in predominantly non-autistic environments. This qualitative study utilized purposive sampling to recruit 15 autistic adults aged 18–28 in the United States. All participants were conversation-level speaking communicators and high school graduates. Each participant engaged in an individual semi-structured, conversational interview with the first author via Zoom video conferences between November 2019 and June 2020. The data analysis identified inductive themes through interpretive phenomenological analysis. Five major themes emerged from the data that captured the challenges of autistic adults: (a) “Communication definitely is a struggle at times”, (b) “if it’s a very comfortable situation, then it’s fine”, (c) my communication style has “been very misunderstood”, (d) “I have to learn people”, and (e) “we’re all human. Autistic too, we’re still human”. The participants’ experiences suggest that differences in their communication style and social behavior resulted in overwhelming feelings of uncertainty and marginalization as they put great effort into engaging with non-autistic individuals.